The Influence of Service Quality and Customer Value on Customer Satisfaction - Fauzi, Ahmad; Purnomo, Yudiyanto (LifeSciFi, 2023)
This study aims to assess the impact of service quality and consumer value on customer satisfaction at PT. Grab Indonesia. The research utilized a descriptive method, employing a Google Form questionnaire designed for random online data collection. The study gathered responses from 114 participants, representing an unknown total population of Grab users. Purposive sampling was applied, with a focus on evaluating the service quality provided by driver partners to enhance consumer satisfaction, comfort, and driver ratings. The collected data was then processed and analyzed. The research revealed that service quality, consumer value, and customer satisfaction all received ratings in the very good category. However, the study did not find any significant influence of service quality on GrabBike customer satisfaction. Consumer value was found to have a partial impact on customer satisfaction, while both service quality and consumer value were observed to partially influence GrabBike customer satisfaction.